DEVELOPMENT OF PROFESSIONAL COMPETENCES OF FUTURE FOREIGN LANGUAGE TEACHERS - Nodira Ahmedova; Gulsanam Nematova; Nilufar Abdanbekova; Rashit Ibragimov (The Bioscan, 2024)
This article is devoted to the development of professional competences of future foreign language teachers, in which the strategies of mastering students’ reading and writing skills and the characteristics of the competence approach are analyzed. Also, the effectiveness of innovative technologies in the development of professional competencies is revealed.